MUSYAWARAH BERWAWASAN INTEGRATIF - Rezita Aprilia, Reno (Penerbit CV Tentrem Karya Nusa, 2019)
Building Indonesian people nationals with character and dignified means integrating social education based on religion and social education based on citizenship. In general, th dynamics of human life can not be separated from a problem that hinders the course of life, Muslims who obey religion and obey the rules of the country will always open the horizon that the Indonesian nation is a nation born on the basis of law by the founders of the Indonesian state organized into Pancasila and laws by looking at religious conditions, beliefs, ethnic and cultural differences. The majority of Indonesian citizens are Muslim. The author provides an explanation of deliberation based on the Qur'an and Haditsh, as well as deliberation in the basis of the Pancasila law and the law namely ?populistism led by wisdom in the policy of representative deliberation